Occurrence of symbiotic fungi and rhizospheric phosphate solubilization in weeds - doi: 10.4025/actasciagron.v35i1.15047 - Edson Aparecido dos Santos; Lino Roberto Ferreira; Mauricio Dutra Costa; Marliane de Cássia Soares da Silva; Marcelo Rodrigues dos Reis; André Cabral França (Acta Scientiarum. Agronomy, 2012)
Studies on the ecology of the organisms involved in the production process are necessary for the development of sustainable agriculture, and sustainability is currently closely linked to the profitability of production. The objective of this study was to verify the occurrence of arbuscular mycorrhizal fungi in weeds infesting Brazilian crops and to evaluate the inorganic phosphate solubilization potential of the associated microbiota. A total of 36 weed species were evaluated for the occurrence of mycorrhizae; of these, 11 were selected to evaluate their potential for total and relative phosphate solubilization. All of the species demonstrated mycorrhizal colonization, including a member of the Brassicaceae family, which is usually assumed to be non-mycorrhizal. In most of the species, morphological types of arbuscular and coiled hyphae were observed, with the coiled hyphae being the most common in the grasses. Dark septate endophytic fungi were observed in most of the plants. The weeds presented different potentials for P solubilization in the rhizosphere; Amaranthus retroflexus, Bidens pilosa and Leonotis nepetaefolia showed high values of relative phosphate solubilization. This is the first report on the mycorrhizae and phosphate solubilization activity in weeds in Brazil.